Kondisi Tenaga Pendidik di Indonesia Timur: Keterkaitan Jumlah Guru Menurut Kelompok Umur di Maluku, Maluku Utara, Bengkulu, dan Papua - Muhammad Rifaldi Akbar; Gentra Ramadhan; Haykal Aiman Rayyan; Pandu Erlangga (CV. Multi Kreasi Media, 2024)
This journal focuses on the condition of the teaching workforce in Eastern Indonesia, particularly in the provinces of Maluku, North Maluku, Bengkulu and Papua. Using a quantitative approach, we analyze the relationship between the number of teachers and principals by age group, as well as the challenges faced in the supply of educators. The results show an imbalance between the number of teachers and principals, with the majority of teachers over 50 years old and less than 30% of teachers under 30 years old. In addition, remote areas have difficulty in attracting qualified educators. To address these issues, we recommend providing incentives for teachers who teach in remote areas, continuous training programs, collaboration between the government and educational institutions, and improved access to educational resources. With these measures, it is hoped that the quality of education in Eastern Indonesia can be significantly improved.